Das Internet und die Transformation der Musikindustrie: Rekonstruktion und Erklärung eines unkontrollierten sektoralen Wandels - Ulrich Dolata (Max Planck Institute for the Study of Societies, 2008)
Since the late 1990s, the music business has been experiencing a period of crisis. A new set of technologies digitization, data compression and the Internet - has forced significant changes on the industry. This paper analyzes the repercussions of this new technological constellation on the socioeconomic structures and institutions of the sector to show that the constitutive impulses for restructuring came from the fringes of the industry and from external actors. Established companies in the music business were hesitant to meet these new technological challenges. They initially reacted with blockades and containment strategies, and only repositioned themselves strategically when the pressure to change grew massive and unavoidable. This paper argues that there were several factors in play that thwarted the ability to anticipate and adapt to these technological, organizational and institutional challenges. These include (1) general difficulties in anticipating the socioeconomic impact of fundamentally new technological opportunities; (2) the complex and time-consuming process of establishing a new techno-institutional match; (3) the sector's technological conservatism and (4) oligopolistic structure along with (5) the structural hierarchy in companies at the center. Taken together, these factors prevented the established core players from effecting a controlled transformation of the sector.
Keywords: 300; Musikwirtschaft; Internet; Digitale Güter; Reorganisation; Strukturwandel; Welt